2017
DOI: 10.1080/13880209.2017.1309054
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi associated with Monarda citriodora, an aromatic and medicinal plant and their biocontrol potential

Abstract: Context: The Food and Agriculture Organization has estimated that every year considerable losses of the food crops occur due to plant diseases. Although fungicides are extensively used for management of plant diseases, they are expensive and hazardous to the environment and human health. Alternatively, biological control is the safe way to overcome the effects of plant diseases and to sustain agriculture. Since Monarda citriodora Cerv. ex Lag. (Lamiaceae/Labiatae) is known for its antifungal properties, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Besides emphasizing the need of a thorough revision of strains currently classified as C. cladosporioides and C. pseudocladosporioides , by the finding of two novel species our study confirms the taxonomic heterogeneity of the Cladosporium complex associated with flowers of Lamiaceae. Indeed, these plants represent a fruitful investigational ground for studying diversity of these ubiquitous fungi, also with reference to the possible contribution by endophytic strains to the biosynthesis of components of essential oils and other bioactive compounds, representing the basic property sustaining their industrial exploitation [ 29 , 30 , 31 , 32 ]. Interestingly, two isolates of each new species were found in two ecologically homogeneous areas in Poland and in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides emphasizing the need of a thorough revision of strains currently classified as C. cladosporioides and C. pseudocladosporioides , by the finding of two novel species our study confirms the taxonomic heterogeneity of the Cladosporium complex associated with flowers of Lamiaceae. Indeed, these plants represent a fruitful investigational ground for studying diversity of these ubiquitous fungi, also with reference to the possible contribution by endophytic strains to the biosynthesis of components of essential oils and other bioactive compounds, representing the basic property sustaining their industrial exploitation [ 29 , 30 , 31 , 32 ]. Interestingly, two isolates of each new species were found in two ecologically homogeneous areas in Poland and in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Soil fungal communities may also play crucial roles as biological control agents for associated plant species (Katoch and Pull, 2017;Singh et al, 2017). In agriculture, fungi are often used as biological control agents active against pests or pathogens through competition for nutrients and space, or as parasites of pests and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that endophytic fungi from plants exhibit antagonistic effect towards phytopathogenic fungi (Mejia et al 2008;Lahlali and Hijri 2010;Kusari et al 2013;Katoch and Pull 2017). The results revealed that the endophytic fungi Neocosmospora sp.…”
Section: Discussionmentioning
confidence: 94%